Speaking to you contemporary poetry and public address - Pollard, Natalie (Oxford : Oxford University Press, 2012)
This volume explores the work of four important poets writing post-1960 - Don Paterson, Geoffrey Hill, W.S. Graham, and C.H. Sissons - in order to show how contemporary British poetry's creative handling of addresses to 'you' are key in its interactions with readers, critics, lovers, editors, fellow poets, and deceased forebears.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Includes bibliographical references and index.
Keywords: Poetics; Hill, Geoffrey -- Criticism and interpretation; Graham, W. S. -- 1918-1986 -- Criticism and interpretation; Sisson, C. H. -- 1914-2003 -- Criticism and interpretation; Forms of address in literature; You (The English word) in literature